(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Urinary bladder diseases are one of the clinical problems encountered in our daily practice.The incidence of these diseases rises with advanced age. These diseases are diagnosed clinically andconfirmed by various non invasive as well as invasive procedures and wall abnormalities are themost important indicator to diagnose such diseases. All these conditions require medical and surgicalintervention. Thereby knowledge regarding normal capacity of urinary bladder is essential to determinethe physiologic variation of this organ. Therefore, full knowledge about gross and histological features ofthe urinary bladder has hard & fast implication for the investigation, diagnosis and further management.With this background the present study has been designed to evaluate the capacity of urine in postmortemhuman urinary bladder. Objectives: To identify the socio-demographic determinants and to determine thecapacity of urine in post mortem human urinary bladder. Materials and Methods: This was a descriptivetype of longitudinal study. Sample size was estimated by reviewing literatures and by expert opinion and70 human postmortem urinary bladders fulfilling the inclusion and exclusion criteria were selected in thisstudy. This study was conducted in the Department of Anatomy, Sylhet MAG Osmani Medical College,Sylhet in collaboration with the Department of Forensic Medicine, Sylhet MAG Osmani Medical College,Sylhet from 1st January 2015 to 31st December 2015. Results: The age of the cadaver ranged from 10 to65 years with the mean age of 32.20 (SD ± 14.38) years; 15 (21.40%) cadavers were in the age group of10-20 years, 36 (51.4%) cadavers were in the age group of 21-40 years and 19 (27.1%) cadavers werein the age group 41-65 years. There were 52 (74.3%) male and 18 (25.7%) female with a ratio of maleto female was 2.89:1. The mean capacity was 35.23 (SD ± 7.48) ml. The mean capacity of the urinarybladder was 31.20 ml (SD ± 7.28); 37.92 ml (SD ± 7.31) and 33.32 ml (SD ± 6.13) in the age group of A,B and C respectively. The difference between group A and B was highly significant (p=0.004); betweengroup B and C was significant (p=0.023); but not significant between group A and C (p=0.364). The meancapacity of urinary bladder of male and female did not differ significantly in age group A (p=0.117),group B (p=0.145) and group C (p=0.241). Conclusion: The gross capacity of urinary bladder was foundincreased with age up to certain limit then slightly decreased in the late age. But the capacity did not differsignificantly between male and female. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.170-176